Preparation method and application of polyhedral oligomeric silsesquioxane / carbon quantum dot composite material

By heating the reaction of polyethylene glycol-cage polysilsesquioxane, perylene and potassium persulfate in formamide solution, the problem of poor interface compatibility in synthesis of POSS and carbon quantum dots is solved, and high efficiency and low The preparation of costly cage polysilsesquioxane/carbon quantum dot composites significantly improves its performance and stability in cell imaging.

CN119119736APending Publication Date: 2024-12-13亳州市人民医院 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411272413.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing POSS and carbon quantum dot synthesis methods have problems such as poor interface compatibility, uneven dispersion and poor repeatability, which affects the application of composite materials in cell imaging.

Method used

The cage polysilsesquioxane/carbon quantum dot composite material is synthesized by one-step method to improve the interface Compatibility and improve material properties.

Benefits of technology

Achieve high yield and low cost fluorescent nanoparticles preparation, significantly improve the biocompatibility and imaging performance of the material, enhance interface compatibility and material stability, and provide better regulatory means to customize the properties of carbon quantum dots. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119736A_ABST
    Figure CN119119736A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a polyhedral oligomeric silsesquioxane / carbon quantum dot composite material and application of the polyhedral oligomeric silsesquioxane / carbon quantum dot composite material in cell imaging. According to the preparation method, dye perylene is adopted as a carbon source, and the dye perylene and polyethylene glycol-polyhedral oligomeric silsesquioxane are synthesized in one step through a heating method. Compared with an existing preparation method, the process has the remarkable advantages that the reaction process is simple, convenient and rapid, complex and harsh reaction conditions are avoided, and the required raw materials are simple in structure, low in cost and easy to obtain. In addition, the method can produce the fluorescent nanoparticles with high yield, can be successfully applied to cell imaging, and shows excellent biocompatibility and imaging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a cage-type polysilsesquioxane / carbon quantum dot composite material and application thereof in cell imaging. Background Art

[0002] Carbon Quantum Dots (CQDs) are a new type of nanomaterials. Due to their excellent fluorescence properties, good biocompatibility and low toxicity, they have been widely used in the field of cell fluorescence imaging. They provide new tools for biomedical research and diagnosis, especially in cell labeling, tracking and disease diagnosis. CQDs can penetrate biological tissues and provide clear images of the internal structure of cells. By changing their size, shape or doping elements to adjust their fluorescence properties, they can emit light of different colors and achieve multi-color imaging. However, their tiny size poses challenges in the preparation, collection and purification process. .

[0003] Cage-type polysilsesquioxane (POSS) nanoparticles, as unique inorganic-organic hybrid materials, are composed of a silicon-oxygen core and surrounding organic groups. This unique structure not only gives POSS nanoparticles excellent mechanical and thermal stability, but also enhances their chemical diversity, making them widely used in many fields such as biomedical imaging, catalysis, and composite material preparation. Especially in the field of biomedical imaging, POSS nanoparticles are very suitable as contrast agents to improve the quality of magnetic resonance imaging or optical imaging, providing better contrast and clarity. In addition, through surface functionalization, POSS nanoparticles can carry specific biomarkers or fluorophores for cell labeling and tracking. They also show good biocompatibility and tunable biodegradability, making them particularly useful in long-term imaging and targeted delivery systems.

[0004] By combining POSS with carbon quantum dots and taking advantage of the unique structure of POSS to encapsulate and purify carbon quantum dots, the combination of this composite nanoparticle in cell imaging can bring significant innovation and breakthroughs. This multifunctional nanocomposite not only enhances the fluorescence performance and improves the imaging quality and accuracy, but also improves the biocompatibility and stability of the material and reduces the potential biotoxicity. In addition, these composites can be used for targeted imaging of specific cells or tissues, improving the specificity and accuracy of imaging. The application of this composite material is also promising in the development of sensors and biomarkers, which can monitor and track specific molecules or biological processes within cells. In terms of drug delivery and therapy, this nanocomposite can provide more effective targeted treatment options while monitoring drug release and distribution through fluorescence imaging technology. In the field of tissue engineering and regenerative medicine, these materials can be used to study cell growth, differentiation and tissue regeneration processes.

[0005] Currently, the main method for synthesizing POSS and carbon quantum dots is the physical mixing method, but there are still problems such as poor interface compatibility between POSS and carbon quantum dots, uneven dispersion of carbon quantum dots in the POSS matrix, and poor repeatability between different batches. Summary of the invention

[0006] In view of the above problems, the present invention provides a method for preparing a cage-type polysilsesquioxane / carbon quantum dot composite material and its application in cell imaging.

[0007] In order to achieve the above technical objectives, a technical solution of the present invention is:

[0008] A method for preparing a cage-type polysilsesquioxane / carbon quantum dot composite material, comprising the steps of:

[0009] S1, dispersing polyethylene glycol-cage polysilsesquioxane (PEG-POSS), perylene and potassium persulfate in a formamide solution and fully mixing, then heating to fully react to obtain a cage polysilsesquioxane / carbon quantum dot solution, and cooling to room temperature;

[0010] S2, centrifugally purify the cage-type polysilsesquioxane / carbon quantum dot solution, and collect it by vacuum drying to obtain a cage-type polysilsesquioxane / carbon quantum dot composite material.

[0011] The above technical solution has the following advantages:

[0012] This method uses the dye perylene as a carbon source and synthesizes a composite fluorescent nanoparticle in one step by heating with polyethylene glycol-cage polysilsesquioxane. Compared with the existing preparation methods, this process has significant advantages: not only is the reaction process simple and rapid, avoiding complex and harsh reaction conditions, but also the required raw materials have a simple structure, low cost and easy to obtain. In addition, this method can produce fluorescent nanoparticles with a high yield and can be successfully used in cell imaging, demonstrating excellent biocompatibility and imaging performance. The fluorescent cage polysilsesquioxane / carbon quantum dots prepared by this method can be used in chemistry, biology, materials science and other fields.

[0013] Compared with the existing preparation methods, the in-situ synthesized carbon quantum dot / cage-type polysilsesquioxane composite nanoparticles of the present invention allow for the formation of stronger chemical or physical bonds between cage-type polysilsesquioxane and carbon quantum dots at the molecular level, thereby improving the interfacial compatibility and overall material properties of the two, and can more effectively control the size, shape and distribution of carbon quantum dots, providing more regulatory means to customize the specific properties of carbon quantum dot materials.

[0014] Preferably, step S1 specifically includes:

[0015] Take a portion of the formamide solution;

[0016] Then, polyethylene glycol-cage polysilsesquioxane, perylene and potassium persulfate are ultrasonically dispersed in the aforementioned formamide solution in sequence;

[0017] The dispersed solution is mixed and heated to 75-80° C. for 30-40 minutes to promote the formation of cage-type polysilsesquioxane / carbon quantum dots to obtain a cage-type polysilsesquioxane / carbon quantum dot solution, which is then cooled to room temperature.

[0018] Preferably, the mass fraction of the polyethylene glycol-cage polysilsesquioxane in the formamide solution is 3.6-4.4 mg / mL.

[0019] Preferably, the mass fraction of perylene in the formamide solution is 6.75-8.25 mg / mL.

[0020] Preferably, the mass fraction of potassium persulfate in the formamide solution is 7.2-8.8 mg / mL.

[0021] Preferably, the heating is carried out under the protection of nitrogen and the temperature gradient does not exceed 1°C / min.

[0022] As an improvement, in step S1, the mass ratio of perylene to potassium persulfate is 0.9:1-0.95:1.

[0023] Preferably, the centrifugal speed in step S2 is 10000 rpm / min, and the centrifugal purification is performed more than 3 times.

[0024] Preferably, the vacuum drying temperature in step S2 is 50-70° C., and the drying time is 8-12 hours.

[0025] In order to achieve the above technical objectives, another technical solution of the present invention is:

[0026] The cage-type polysilsesquioxane / carbon quantum dots composite material prepared by the above preparation method is applied to cell imaging, and the cage-type polysilsesquioxane / carbon quantum dots are added to cells as fluorescent markers, and the labeling of the cells by the cage-type polysilsesquioxane / carbon quantum dots is observed and recorded using a fluorescence microscope. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A schematic diagram of the one-step synthesis of cage-type polysilsesquioxane / carbon quantum dots according to the present invention;

[0028] Figure 2 The transmission electron microscope image of the prepared cage-type polysilsesquioxane / carbon quantum dots;

[0029] Figure 3 The following are photos of the prepared cage-type polysilsesquioxane / carbon quantum dots under ambient light and ultraviolet light;

[0030] Figure 4 is the fluorescence emission spectrum of the prepared cage-type polysilsesquioxane / carbon quantum dots;

[0031] Figure 5 This is a cell imaging picture of the prepared cage-type polysilsesquioxane / carbon quantum dots. DETAILED DESCRIPTION

[0032] The embodiments of the present invention are described in detail with reference to the accompanying drawings, but no limitation is imposed on the claims of the present invention.

[0033] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0034] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0035] The present invention is further described below by means of specific examples, but the present invention is not limited thereto.

[0036] 1. Preparation of cage-type polysilsesquioxane / carbon quantum dot materials;

[0037] Example 1

[0038] 0.36g of polyethylene glycol-cage polysilsesquioxane (PEG-POSS), 0.675g of perylene and 0.72g of potassium persulfate were mixed in 100mL of formamide solution (concentration of 99.5%), and fully mixed by ultrasonic dispersion. The mixed solution was heated to a relatively low temperature of 75-80°C, kept for 30-40 minutes, and the heating temperature was heated under the protection of nitrogen and the temperature gradient was no more than 1°C / min, to promote the formation of cage-type polysilsesquioxane / carbon quantum dots. During the reaction, the solution color was converted into a yellow-green color under natural light. After three centrifugations at 10000rpm / min for ten minutes, the obtained precipitation was dried and collected under vacuum (vacuum drying temperature was 50-70°C, and drying time was 8-12 hours), and cage-type polysilsesquioxane / carbon quantum dot composite materials were obtained.

[0039] Example 2

[0040] 0.4g of polyethylene glycol-cage polysilsesquioxane (PEG-POSS), 0.75g of perylene and 0.8g of potassium persulfate were mixed in 100mL of formamide solution (concentration of 99.5%), and fully mixed by ultrasonic dispersion. The mixed solution was heated to a relatively low temperature of 75-80°C for 30-40 minutes, and the heating temperature was heated under the protection of nitrogen and the temperature gradient was no more than 1°C / min to promote the formation of cage-type polysilsesquioxane / carbon quantum dots. During the reaction, the solution color was converted into a yellow-green color under natural light. After three centrifugations at 10000rpm / min for ten minutes, the obtained precipitation was dried and collected under vacuum (vacuum drying temperature was 50-70°C, and drying time was 8-12 hours), and cage-type polysilsesquioxane / carbon quantum dot composite materials were obtained.

[0041] Example 3

[0042] 0.44g of polyethylene glycol-cage polysilsesquioxane (PEG-POSS), 0.825g of perylene and 0.88g of potassium persulfate were mixed in 100mL of formamide solution (concentration of 99.5%), and fully mixed by ultrasonic dispersion. The mixed solution was heated to a relatively low temperature of 75-80°C, kept for 30-40 minutes, and the heating temperature was heated under the protection of nitrogen and the temperature gradient was no more than 1°C / min, to promote the formation of cage-type polysilsesquioxane / carbon quantum dots. During the reaction, the solution color was converted into a yellow-green color under natural light. After three centrifugations at 10000rpm / min for ten minutes, the obtained precipitation was dried and collected under vacuum (vacuum drying temperature was 50-70°C, and drying time was 8-12 hours), and cage-type polysilsesquioxane / carbon quantum dot composite materials were obtained.

[0043] When the preparation method of the present invention is actually applied, it is not limited to the composition ratio relationship given in the above three embodiments, as long as the following composition ratio conditions are met:

[0044] (1) The mass fraction of polyethylene glycol-cage polysilsesquioxane in the formamide solution is 3.6-4.4 mg / mL.

[0045] (2) The mass fraction of perylene in formamide solution is 6.75-8.25 mg / mL.

[0046] (3) The mass fraction of potassium persulfate in formamide solution is 7.2-8.8 mg / mL.

[0047] Furthermore, in order to achieve better effects, the mass ratio of perylene to potassium persulfate may be limited to within the range of 0.9:1-0.95:1.

[0048] 2. Characterization of cage-type polysilsesquioxane / carbon quantum dots:

[0049] 1. Transmission Electron Microscopy Characterization

[0050] like Figure 2 As shown, through transmission electron microscopy observation, the cage-type polysilsesquioxane / carbon quantum dot composite material prepared by the method of the present invention is a nearly spherical carbon quantum dot / cage-type polysilsesquioxane core-shell structure, wherein the carbon quantum dots embedded in the cage-type polysilsesquioxane matrix are spherical in shape and have a size of about 6 nm;

[0051] 2. Emission wavelength;

[0052] The prepared cage-type polysilsesquioxane / carbon quantum dot composite material is dispersed in deionized water to obtain a cage-type polysilsesquioxane / carbon quantum dot solution. Figure 3 As shown, the caged polysilsesquioxane / carbon quantum dot solution emits bright green light under ultraviolet light. The excitation wavelength of the caged polysilsesquioxane / carbon quantum dot (i.e., the wavelength of ultraviolet light used for irradiation) ranges from 320 to 420 nm, preferably from 330 to 370 nm, and optimally from 340 to 360 nm.

[0053] like Figure 4 As shown, according to the data obtained by spectrometer analysis, the emission wavelength of cage-type polysilsesquioxane / carbon quantum dots is 420-650nm, and the maximum emission wavelength is 530nm.

[0054] 3. Biological Applications of Cage-type Polysilsesquioxane / Carbon Quantum Dots

[0055] Using a medium suitable for the growth of MCF-7 cells (Michigan Cancer Foundation–7, human breast cancer cells), seed the MCF-7 cells at an appropriate density in a culture dish suitable for fluorescence microscopy imaging, such as a glass-bottom culture dish or a transparent cell culture plate;

[0056] The cage-type polysilsesquioxane / carbon quantum dot material prepared by the method of the present invention is dispersed in phosphate buffered saline (PBS) to a mass fraction of 10-100 μg / mL, thereby preparing a cage-type polysilsesquioxane / carbon quantum dot PBS solution;

[0057] Adding a PBS solution of caged polysilsesquioxane / carbon quantum dots into the cell culture medium, and incubating with the cells for a certain period of time, 1-24 hours, so that the POSS / carbon quantum dots can enter the interior of the cells;

[0058] After the co-incubation, the cells were gently washed 2-3 times with PBS to remove the POSS / carbon quantum dots that did not enter the cells.

[0059] The MCF-7 cells cultured with the caged polysilsesquioxane / carbon quantum dots were imaged and observed using a laser confocal microscope. According to the fluorescence characteristics of the caged polysilsesquioxane / carbon quantum dots, an excitation wavelength of 355 nm and an emission wavelength of 530 nm were selected.

[0060] like Figure 5 As shown, it is a cell imaging picture of the cage-type polysilsesquioxane / carbon quantum dots prepared according to the method of the present invention. By analyzing the fluorescence image using image processing software, the distribution of the cage-type polysilsesquioxane / carbon quantum dots in the cell can be evaluated, the fluorescence intensity can be quantitatively analyzed, etc.

[0061] Based on the results of fluorescence imaging, the intracellular localization of cage-type polysilsesquioxane / carbon quantum dots, the cellular uptake efficiency, and the interaction between carbon quantum dots and cells can be analyzed.

[0062] In the above method:

[0063] The entire process can be stirred using a polytetrafluoroethylene stirring bar that has been cleaned in sequence with acetone, alcohol, and deionized water, which can prevent the reactants from being contaminated and allow the materials to react fully or be evenly dispersed.

[0064] In summary, the present invention has the following advantages:

[0065] 1. The thermal solution method for synthesizing cage-type polysilsesquioxane / carbon quantum dots has low cost, high yield and high luminescence efficiency.

[0066] 2. Cage-type polysilsesquioxane / carbon quantum dots have good biocompatibility, which further improves the stability of carbon quantum dots, prevents them from photobleaching or degradation in biological environments, and thus prolongs the fluorescence lifetime.

[0067] 3. Cage-type polysilsesquioxane has good biocompatibility and low toxicity, making the application of cage-type polysilsesquioxane / carbon quantum dot composite materials in vivo safer. The introduction of cage-type polysilsesquioxane can effectively reduce the biological toxicity that carbon quantum dots may produce and improve their application potential in biomedical imaging.

[0068] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. A method for preparing a cage-type polysilsesquioxane / carbon quantum dot composite material, comprising the steps of: S1, dispersing polyethylene glycol-cage polysilsesquioxane, perylene and potassium persulfate in a formamide solution and fully mixing, then heating to fully react to obtain a cage polysilsesquioxane / carbon quantum dot solution, and cooling to room temperature; S2, centrifugally purify the cage-type polysilsesquioxane / carbon quantum dot solution, and collect it by vacuum drying to obtain a cage-type polysilsesquioxane / carbon quantum dot composite material.

2. The method for preparing the cage-type polysilsesquioxane / carbon quantum dot composite material according to claim 1, characterized in that: Step S1 specifically includes: Take a portion of the formamide solution; Then, polyethylene glycol-cage polysilsesquioxane, perylene and potassium persulfate are ultrasonically dispersed in the aforementioned formamide solution in sequence; The dispersed solution is heated to 75-80° C. and maintained for 30-40 minutes to promote the formation of cage-type polysilsesquioxane / carbon quantum dots to obtain a cage-type polysilsesquioxane / carbon quantum dot solution, and then cooled to room temperature.

3. The method for preparing the cage-type polysilsesquioxane / carbon quantum dot composite material according to claim 1, characterized in that: The mass fraction of the polyethylene glycol-cage-shaped polysilsesquioxane in the formamide solution is 3.6-4.4 mg / mL.

4. The method for preparing the cage-type polysilsesquioxane / carbon quantum dot composite material according to claim 1, characterized in that: The mass fraction of the perylene in the formamide solution is 6.75-8.25 mg / mL.

5. The method for preparing the cage-type polysilsesquioxane / carbon quantum dot composite material according to claim 1, characterized in that: The mass fraction of the potassium persulfate in the formamide solution is 7.2-8.8 mg / mL.

6. The method for preparing the cage-type polysilsesquioxane / carbon quantum dot composite material according to claim 1, characterized in that: The heating is carried out under the protection of nitrogen and the temperature gradient does not exceed 1°C / min.

7. The method for preparing the cage-type polysilsesquioxane / carbon quantum dot composite material according to claim 1, characterized in that: In the step S1, the mass ratio of perylene to potassium persulfate is 0.9:1-0.95:

1.

8. The method for preparing the cage-type polysilsesquioxane / carbon quantum dot composite material according to claim 1, characterized in that: In step S2, the centrifugal speed is 10000 rpm / min, and the centrifugal purification is performed more than 3 times.

9. The method for preparing the cage-type polysilsesquioxane / carbon quantum dot composite material according to claim 1, characterized in that: In step S2, the vacuum drying temperature is 50-70° C., and the drying time is 8-12 hours.

10. Application of the cage-type polysilsesquioxane / carbon quantum dot composite material prepared by the preparation method according to any one of claims 1 to 9 in cell imaging, characterized in that: Cage-type polysilsesquioxane / carbon quantum dots were used as fluorescent markers and added into cells, and the labeling of cells by cage-type polysilsesquioxane / carbon quantum dots was observed and recorded using a microscope.